2022
DOI: 10.3389/fendo.2022.850698
|View full text |Cite
|
Sign up to set email alerts
|

Value of Contrast-Enhanced Ultrasound in Mummified Thyroid Nodules

Abstract: Mummified thyroid nodules (MTNs) are rarely reported and are usually misdiagnosed as malignant nodules. This article first reviewed the contrast-enhanced ultrasound (CEUS) enhancement features of 218 MTNs and classified them into three (A, B, C) patterns. The A pattern MTNs show linear hypo-enhancement, the B pattern MTNs show heterogeneous hypo-enhancement, and the C pattern MTNs show no enhancement in thyroid nodules. The A and C pattern enhancements of MTNs demonstrated a high specificity compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Moreover, some hypoechoic Hashimoto nodules with blurred margins can be classified as C-TIRADS 4 ( 8 ). and mummified nodules with internal necrotic components may also exhibit marked hypoechogenicity ( 9 ). Distinguishing these from malignant nodules poses challenges, leading to the low specificity of 2D-US and warranting fine needle aspiration (FNA), an invasive procedure ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some hypoechoic Hashimoto nodules with blurred margins can be classified as C-TIRADS 4 ( 8 ). and mummified nodules with internal necrotic components may also exhibit marked hypoechogenicity ( 9 ). Distinguishing these from malignant nodules poses challenges, leading to the low specificity of 2D-US and warranting fine needle aspiration (FNA), an invasive procedure ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that it was difficult to differentiate the microvasculature within lesions using color Doppler flow imaging (CDFI) and power Doppler imaging (PDI) ( 15 ). Although contrast-enhanced US (CEUS) can be used to distinguish MTNs and PTCs, it is relatively invasive and the contrast agents may cause allergic reactions ( 16 ). Superb microvascular imaging (SMI) is an innovative microvascular US imaging technique that can separate low-speed flow signals from motion artifacts by multidimensional filtering ( 17 ).…”
Section: Introductionmentioning
confidence: 99%